Barnehageledelse i endring - Kjetil Børhaug; Dag Øivind Lotsberg (Nordisk Barnehageforskning, 2010)
Title: Changing pre-school management Abstract: Management of Norwegian preschools evolves in a context which is rapidly changing. In this article, it is argued that due to such changes, management of the preschool’s relation to its environment as well as management concerning the educational quality of the preschool must be assumed to gain in importance. According to previous research both these areas are neglected by preschool management. Ten preschool directors are interviewed depth about their tasks, and it is argued that management focuses both on educational quality as wellas on external relations.